Hedge Funds, Systemic Risk, and Dodd-Frank - Lloyd Dixon, Noreen Clancy, and Krishna B. Kumar (RAND Corporation, 2013)
D.C., to discuss the ways hedge funds might contribute to systemic risk and the extent to which recent financial reforms have addressed these potential risks. Invited participants included thought leaders from industry, government, and academia. Regulatory perspectives were represented by senior staff from the U.S. Department of the Treasury, the Federal Reserve Board of Governors, the Financial Crisis Inquiry Commission, and the House Financial Services Committee. Individuals involved in various aspects of the hedge-fund industry brought the private-sector perspective, and academics and RAND staff brought a policy analysis perspective. The symposium participants are listed in Appendix A. These proceedings summarize the major themes and issues raised during the symposium. The goal of the symposium was to inform the discussion on the issues that should be addressed regarding the potential for hedge funds to increase systemic risk and the appropriate policy response. To enhance the free flow of ideas, participants were promised that the symposium proceedings would not attribute comments and observations to individuals or their organizations. Readers of these proceedings may also be interested in the following RAND document, which was used to help structure the dialogue during the symposium: Lloyd Dixon, Noreen Clancy, Krishna B. Kumar, Hedge Funds and Systemic Risk, Santa Monica, Calif.: RAND Corporation, MG-1236-CCEG, 2012.1